2022
DOI: 10.1002/advs.202201586
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Water‐Evaporation‐Induced Electricity Based on Liquid–Solid Triboelectric Nanogenerator

Abstract: Harvesting energy from natural water evaporation has been proposed as a promising alternative to supply power for self‐powered and low‐power devices and systems, owing to its spontaneous, ubiquitous, and sustainability. Herein, an approach is presented for harvesting water‐evaporation‐induced electricity based on liquid–solid triboelectric nanogenerators (LS‐TENGs), which has various advantages of easy preparation, substrate needless, and robustness. This developed harvester with porous Al2O3 ceramic sheet can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 47 publications
0
50
0
Order By: Relevance
“…In fact, both the V oc and I sc values slightly increased with temperature mainly because of facilitated sorption and diffusion of ions in the device. 1,42 In particular, the I sc substantially increased at 80 °C. Notably, because of the antifreezing characteristics of the organohydrogel, our MAO-MEG device functioned properly even at −20 °C, which is far below the freezing temperature of water.…”
Section: Resultsmentioning
confidence: 94%
“…In fact, both the V oc and I sc values slightly increased with temperature mainly because of facilitated sorption and diffusion of ions in the device. 1,42 In particular, the I sc substantially increased at 80 °C. Notably, because of the antifreezing characteristics of the organohydrogel, our MAO-MEG device functioned properly even at −20 °C, which is far below the freezing temperature of water.…”
Section: Resultsmentioning
confidence: 94%
“…[70,71,72] Liquid-solid CE-based TENG devices play an important role in self-powered sensors and energy harvesting, including but not limited to rain mappers, 3D acceleration sensors for automotive systems, and water wave energy harvesting systems. [73,74,75,76] However, whether the carrier between liquid-solid CEs was ion transfer or electron transfer was still the focus of debate, but with the deepening of research, more and more results showed that the transferred electron was the main carrier of liquidsolid CEs streamer. [50,77] Among them, KPFM has played an important role in the mechanism study of liquid-solid CE mechanism.…”
Section: Applications In the Liquid-solid Contact Electrification Of ...mentioning
confidence: 99%
“…The absence of the application of SiOC screens in relevant engineering fields of application can be attributed to the natural brittleness of porous ceramics and the challenge of producing crackless porous ceramics that allow particle-free phase separation. Porous ceramics can be applied in applications such as catalyst support, energy harvesting, or filtration [ 20 , 21 , 22 ] and may offer some advantages compared to metallic screens such as chemical and thermal stability, relatively lower density, and thermal conductivity [ 23 , 24 ]. Relatively low values of thermal conductivity between 0.2 W m −1 K −1 and 2.0 W m −1 K −1 were reported for porous and non-porous SiOC, respectively, in a temperature range from 77 K to 1400 K [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%